Injectable contraception: what should the longest interval be for reinjections? - Markus J. Steiner (2018)
Background: Progestin-only injectable contraceptives continue to gain in popularity, but uncertainty remains about pregnancy risk among women late for reinjection. The World Health Organization (WHO) recommends a "grace period" of 2 weeks after the scheduled 13-week reinjection. Beyond 2 weeks, however, many providers send late clients home to await menses. Study design: A prospective cohort study in Uganda, Zimbabwe and Thailand followed users of depot-medroxyprogesterone acetate (DMPA) for up to 24 months. Users were tested for pregnancy at every reinjection, allowing analysis of pregnancy risk among late comers. Results: The analysis consists of 2290 participants contributing 13,608 DMPA intervals. The pregnancy risks per 100 women-years for "on time" [0.6; 95% confidence interval (CI), 0.33-0.92], "2-week grace" (0.0; 95% CI, 0.0-1.88) and "4-week grace" (0.4; 95% CI, 0.01-2.29) injections were low and virtually identical. Conclusion: Extending the current WHO grace period for DMPA reinjection from 2 to 4 weeks does not increase pregnancy risk and could increase contraceptive continuation. © 2008.